Error Analysis of Student’s Descriptive Text Writing Using Grammarly Software - Abubakar, Intan S.; Napu, Novriyanto; Dama, Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One of the English skills which is important to be mastered by students is writing skills. Writing is creative and expressive process. Students need to explore their ideas to write comprehensively. However, there are still many students who make mistakes in writing. This study aims to determine the types of errors most often made by students in writing descriptive text with Grammarly software. Qualitative research design was used in this study. Error analysis in student writing with Grammarly software was applied to 2 classes with a total of 20 English education students. This research is expected to provide valuable insights into good writing procedures, especially in descriptive text writing and the use of Grammarly (AI) software platforms in improving students’ writing skills. The results of the research on error analysis and error classification with Grammarly software show that there are 4 errors made by students in writing descriptive text, namely correctness 46 (51%) errors, clarity 28 (31%) errors, engagement 11 (12%) errors and delivery 5 (6%) errors. With correctness 46 errors and clarity 28 errors as the most frequent types of errors made by students. These findings indicate that students need to improve their writing skills by utilizing the available Grammarly software platforms (AI).